The Youth Anti-Soviet Resistance Movement in Lithuania in the Seventies and Eighties - Račkauskaitė, Živilė (Genocidas ir rezistencija, 1998)
The formation of a resistance movement in the totalitarian Soviet system is a unique phenomenon. In Lithuania, the resistance has never been completely absent. As the armed resistance became exhausted, a new form of resistance began to emerge in Lithuania, which many authors refer to as passive resistance. This paper examines the resistance movement of 1960s and 1970s, which included the area of active opposition, characterised by the establishment of various organisations and groups and the production of underground press. To call such a concrete, active and tangible activity as passive resistance is not quite right. Although, in this respect, passivity can be seen as a certain tactic of resistance – a non–violent struggle as opposed to the armed post–war resistance.
Keywords: antisoviet resistance; youth; KGB; samizdat